Can One Novel Series of Transition Metal Complexes of Oxy-dianiline Schiff Base Afford Advances in Both Biological Inorganic Chemistry and Materials Science?. Issue 1 (2nd January 2022) - Deghadi, Reem G.; Elsharkawy, Ahmed E.; Ashmawy, Ashraf M.; Mohamed, Gehad G.
ABSTRACT: This paper provides a manifestation of a new tradition by which Comments on Inorganic Chemistry starts publishing original research content that, nonetheless, preserves the Journal's identity as a niche for a critical discussion of contemporary literature in inorganic chemistry; for previous manifestations, see Comments Inorg. Chem. 2020, 40, 277-303 and references cited in the abstract thereof as Yaseen W. K.; Sanders S. F.; Almotawa R. M.; Otten B. M.; Bhat S.; Alamo D. C.; Marpu S. B.; Golden T. D.; Omary M. A. "Are Metal Complexes" Organic, Inorganic, Organometallic, or Metal-Organic Materials? A case Study for the Use of Trinuclear Coinage Metal Complexes as "Metal-Organic Coatings" for Corrosion Suppression on Aluminum Substrates Comments Inorg. Chem. 2019, 39, 1-26 and also, Mohapatra R. K.; Das P. K.; Pradhan M. K.; El-Ajaily M. M.; Das D.; Salem H. F.; Mahanta U.; Badhei G.; Parhi P. K.; Maihub A. A.; Kudrat -E-Zahan Md. "Recent Advances in Urea- and Thiourea-Based Metal Complexes: Biological, Sensor, Optical, and Corrosion Inhibition Studies" Comments Inorg. Chem. 2019, 39, 127-147). In this work, the Schiff base 1-(6-(1-((4-(4-aminophenoxy)phenyl)imino)ethyl)-pyridin-2-yl)ethan-1-one (L) and eight transition metal complexes were synthesized. The reaction of 4, 4-oxy-dianiline with 2, 6-diacetylpyridine in 1:1 molar ratio affords to the ligand which was employed in the synthesis of the corresponding metal complexes by reacting with the Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) chlorides in 1:1 molar ratio. All the compounds were characterized by using different analytical methods. Structures of complexes were found to be octahedral as deduced from the spectroscopic and magnetic moment measurements. The ligand behaves as a neutral tridentate ligand where it coordinated to metal ions through N-azomethine, N-pyridine, and O-carbonyl group. Besides, experimental investigations for their antibacterial activity against different bacteria species were studied, molecular docking studies were reported with receptors 4ME7, 4K3V, 3T88 and 4WJ3. Density functional theory (DFT) calculations for ligand were reported. Finally, the evaluation of corrosion inhibition efficiency was measured by using different techniques such as electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and electrochemical frequency modulation (EFM). Scanning electron microscope (SEM) and energy dispersive X-Ray analysis (EDX) were measured to affirm the presence of barrier film on the carbon steel surface by inspecting the surface morphologies and elemental composition of corrosion products.